Blowout and stability limits of ammonia-hydrogen-nitrogen/air flames in non-premixed coaxial swirl combustor with varying ammonia fraction - Yadav R.; Santhosh R. (My University, 2025)
The present experimental investigation concerns identification of stable flame regimes and blowout limits of ammonia-hydrogen-nitrogen flames in confined coaxial swirling jet configuration with a confinement ratio (CR) of 1.82. Volumetric fraction of ammonia is varied from 20 to 70 %. Methane flames are also tested as benchmark case. Flames are imaged using CCD camera fitted with bandpass filters. The binarized Abel-deconvoluted CH∗ and NH2∗ chemiluminescence images are analysed to classify different flame shape transitions. In the non-premixed coaxial swirl combustor, it is observed that ammonia-hydrogen-nitrogen/air flame with 70 % ammonia behaved similar to methane which is in-line with past studies. The blowout limits and time-averaged flame topological transitions as swirl number was systematically varied were also similar. However, 70 % ammonia blend produced compact flames than that of methane. Also, the lift-off height was shorter. As the ammonia fraction decreases (accompanied by consequent increase in hydrogen fraction in the fuel) the blowout limits increase indicating that a stronger swirling strength of coaxial jet is required to blowout ammonia-lean (or hydrogen-rich) fuel. The flame transition zones also widen. The flames become more compact. All in all, ammonia-hydrogen-nitrogen flames with less than 60 % ammonia fraction behave differently when compared to 70 % ammonia fraction fuel and methane. Lastly, a Reynolds number defined based on velocity characterized by strength of coflow swirl jet is shown to vary linearly with fuel Reynolds number for all the fuels. Finally, an expression involving this Reynolds number is proposed as blowout criteria for ammonia-hydrogen-nitrogen flames within the ammonia fractions tested in the present study. © 2024 The Energy Institute